'It's hard to write a good article': The online comprehension of excuses as indirect replies. Issue 6 (June 2018) - Stewart, Andrew J; Wood, Jeffrey S; Le-luan, Elizabeth; Yao, Bo; Haigh, Matthew
In an eye-tracking experiment, we examined how readers comprehend indirect replies when they are uttered in reply to a direct question. Participants read vignettes that described two characters engaged in dialogue. Each dialogue contained a direct question (e.g., How are you doing in Chemistry? ) answered with an excuse (e.g., The exams are not fair ). In response to direct questions, such indirect replies are typically used to avoid a face-threatening disclosure (e.g., doing badly on the Chemistry course). Our goal was to determine whether readers are sensitive during reading to the indirect meaning communicated by such replies. Of the three contexts we examined, the first described a negative, face-threatening situation and the second a positive, non-face threatening situation, while the third was neutral. Analysis of reading times to the replies provides strong evidence that readers are sensitive online to the face-saving function of indirect replies.